Effects of distiller’s dried grains with solubles on enteric methane emissions in dairy and beef cattle: a meta-analysis - Malik, Muhammad Irfan; Li, Jianping; Capucchio, Maria Teresa; Hassan, Talal; Sun, Xuezhao (Frontiers in Veterinary Science, 2024)
IntroductionDistiller’s dried grains with solubles (DDGS), a by-product of grain fermentation for ethanol production, are extensively used in livestock feed. Given their nutrient composition, DDGS could potentially influence methane (CH4) emissions, a significant greenhouse gas concern in ruminant production systems. This study utilized a multilevel random-effects meta-analysis to assess the impact of DDGS inclusion in cattle diets on CH4 production and yield.MethodsThe literature search was conducted on 23 July 2024. Studies reporting CH4 emissions and dry matter intake (DMI) in cattle fed DDGS-based diets were identified, and data extraction was performed. The meta-analysis calculated the mean difference (MD) for DMI and CH4 yield and the relative mean difference (RMD) for CH4 production across the selected studies.ResultsA total of k = 25 effect sizes from 10 studies were included in the DMI meta-analysis. DDGS had no significant effect on DMI in dairy or beef cattle (p = 0.770, MD = 0.070, 95% confidence interval [CI] from −0.420 to 0.561). For CH4 production, k = 24 effect sizes from 10 studies were analyzed, revealing no significant effect (p = 0.759, RMD = −1.045, 95% CI: from −8.025 to 5.935). Similarly, the meta-regression model indicated that the diet’s ether extract (EE) had no significant influence (p = 0.815, 95% CI from −1.121 to 1.409) on CH4 production. For CH4 yield, k = 23 effect sizes from 10 studies were included, with results showing no significant effect (p = 0.475, MD = −0.434 g/kg DMI, 95% CI: from −1.673 to 0.805). The regression model for the EE content of the diet also showed no significant impact on CH4 yield (p = 0.311, 95% CI: from −0.366 to 0.122).DiscussionThe findings suggest that the inclusion of DDGS does not significantly affect DMI, enteric CH4 production, or CH4 yield in cattle. Moreover, the EE content in DDGS-containing diets does not significantly influence CH4 outcomes. These results indicate that DDGS can be incorporated into cattle diets without exacerbating CH4 emissions, contributing to sustainable livestock feeding practices.